Knowledge and attitude of automotive workers towards noise induced hearing loss - Mohd Zulkefli, Nor Afiah; Rusli, Mohammad Farhan; Abdul Rahman, Anita (Community Health Society Malaysia, 2016)
Background: Excessive exposure to noise can cause a serious irreversible disease known as noise induced hearing loss. In all workplaces there is always risk of exposure to occupational noise but some workers are more susceptible to a higher exposure of workplace noise in comparison to others. This study was to determine the satisfactory knowledge and attitude of automotive workers towards noise induced hearing loss. Materials and Methods: A cross sectional study was conducted from January 2015 to May 2015 in an automotive company in Selangor. There were 457 respondents that were selected based on simple random sampling method, using validated and reliable self-administered questionnaire. The dependent variables were knowledge and attitude on noise induced hearing loss and the independent variables were age, gender, ethnicity, level of education, perceived noise exposure, years of service and training on safety. Data was analysed using SPSS version 22. Result: Response rate was 83.1%. 21.7% had satisfactory knowledge and 39.8% had satisfactory attitude towards noise induced hearing loss. For knowledge the significant association were between age group and (X2=17.831; df 3; p<0.001), perceived noise exposure (X2=6.237; df 2; p=0.044), years in service (X2=618.588; df 3; p<0.001) and training on safety (X2=9.129; df 1; p=0.001) with noise induced hearing loss. As for attitude they were significant association between level of education (X2=20.934; df 3; p<0.001), perceived noise exposure (X2=54.560; df 2; p<0.001) and years in service (X2=19.464; df 3; p<0.001) with noise induced hearing loss. Conclusion: The satisfactory level of knowledge and attitude is low. Heath intervention focussing on knowledge on noise induced hearing loss is needed. The results from this study may be used to set appropriate measures and identify workers who are at risk of developing noise induced hearing loss.